Traumatic Self-Harm in Older People: A 7-Year Descriptive Analysis from a London Major Trauma Centre - Thompson, Joseph H.S.; Sivapathasuntharam, Dhanupriya; Cole, Elaine; Sampson, Elizabeth L (Injury, 2025)
•A small but important proportion of older people presenting with serious self-harm require admission under trauma clinicians.•Older trauma patients presenting with self-harm are predominantly male and sustain penetrating injury mechanisms.•Male patients are most likely to suffer self-stabbing and female patients a jump from height.•The majority of patients have a previous psychiatric history and are frequently discharged to inpatient psychiatric settings.•This study represents the first UK-specific analysis of older trauma patients presenting with serious self-harm. Suicide in older people is increasing. We know less about serious deliberate self-harm in this population or the impact of this on Major Trauma Centres (MTC). Investigate demographics, injury mechanism and outcomes in older people admitted with self-inflicted injury. Retrospective service evaluation. Single MTC in London, UK. 60 people aged 65 years and over admitted to a MTC with self-inflicted injury. Retrospective analysis of trauma registry data (February 2015-2022). Variables: age, sex, past medical and psychiatric history, home and marital status, injury type and narrative, injury severity score (ISS), critical care admission, length of stay, discharge status and destination. Self-inflicted injury represented 1.5 % of trauma admissions aged 65 and over (80 % male, median age 73 years). Most females and over half of men had a psychiatric history (females n = 11, 91.7 %; males n = 28, 58.3 %). Depression was the most common psychiatric comorbidity (n = 15). Males were more likely to suffer penetrating injury (males n = 37, 77.1 %; females n = 4, 33.3 %). The most common injury mechanism was self-stabbing amongst males (n = 37, 77.1 %) and a jump from height amongst females (n = 6, 50.0 %). Median ISS (8.5) and mortality (n = 8, 13.3 %) was low across the cohort. The most common discharge destination was psychiatric admission (males n = 28, 58.3 %; females n = 6, 50.0 %). Older people who present with traumatic self-inflicted injury are predominantly male, utilise violent methods, have significant psychiatric comorbidity and require psychiatric admissions.